2008
DOI: 10.1007/s10826-008-9251-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Peer Relationships in Early Adolescence: The Role of Peer Contact, Self-esteem, and Social Anxiety

Abstract: We examined associations between children's health status and the quality of their peer relationships, as well as factors that may account for individual variation in the quality of chronically ill and healthy children's peer relationships. Our sample included 268 children (138 boys; 130 girls) with 149 European-Americans and 119 AfricanAmericans. There were 91 children with a chronic illness; 35 with asthma, 26 with diabetes, and 30 with obesity. Chronically ill children were characterized by teachers as disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 35 publications
1
17
0
2
Order By: Relevance
“…Establishing positive peer relationships is an important aspect of psychosocial health and development in childhood with implications for normative social adjustment. 41 Chronic illness in youth may contribute to lower levels of social competence, 42 and difficulty with peer relationships is one of the most influential factors on self-esteem and general well-being. 43 Parents in this study recognized that peer relationships and social competence can be an area of vulnerability 42 and children reported a desire to physically "keep up" and be accepted by peers within the context of PA. PA provides an opportunity for peer engagement, acceptance, and the development of relationships, and there is strong evidence that participation with friends is associated with higher levels of PA. 44 Understanding the role that PA plays in children's social and emotional health is valuable information for parents in supporting participation.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing positive peer relationships is an important aspect of psychosocial health and development in childhood with implications for normative social adjustment. 41 Chronic illness in youth may contribute to lower levels of social competence, 42 and difficulty with peer relationships is one of the most influential factors on self-esteem and general well-being. 43 Parents in this study recognized that peer relationships and social competence can be an area of vulnerability 42 and children reported a desire to physically "keep up" and be accepted by peers within the context of PA. PA provides an opportunity for peer engagement, acceptance, and the development of relationships, and there is strong evidence that participation with friends is associated with higher levels of PA. 44 Understanding the role that PA plays in children's social and emotional health is valuable information for parents in supporting participation.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, socially anxious girls were found to be at higher risk for developing depressive symptoms over time due to a greater susceptibility to peer contagion (Prinstein 2007). As socially anxious individuals usually have poor self-esteem (McCarroll et al 2009), they might be more vulnerable to peer contagion-both in close relationships and in the crowd social network. Consequently, socially anxious adolescents may be at increased risk to reinforce their social anxiety because they could be more vulnerable to peer contagion than less socially anxious adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…For socially anxious youths, this might imply that selecting friends who are equally socially anxious might be the best strategy for avoiding social scrutiny. Because social anxiety in early adolescence is linked to poor self-esteem (McCarroll, Lindsey, MacKinnon-Lewis, Campbell Chambers, & Frabutt, 2009) and conformant behaviors (Santee & Maslach, 1982), it is reasonable to think that socially anxious youths might avoid the popular groups to reduce the chance of evaluation by and disagreements with others. Although there is no direct empirical evidence that adolescents select their friends based on similarity of social anxiety, studies of younger children show that shy or withdrawn children tend to be similar to their friends in terms of socially fearful, withdrawn characteristics (Gu¨roglu, Van Lieshout, Haselager, & Scholte, 2007;Haselager, Hartup, Van Lieshout, & Riksen-Walraven, 1998;.…”
mentioning
confidence: 99%